2012
DOI: 10.1007/s00345-012-0882-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary urethral carcinoma in females: an epidemiologic study on demographical factors, histological types, tumour stage and survival

Abstract: Female primary urethral carcinoma is a rare condition, and the majority of patients were aged above 65 years. Almost half of patients have advanced disease upon diagnosis. TNM stage and histological type of disease are the most determining factors for survival. Extended surgery with or without radiotherapy seems to be the most favourable treatment. Awareness and early diagnosis are important to improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 26 publications
5
52
0
1
Order By: Relevance
“…These results are in accordance with prior studies [2,8,9] . For the multivariable analysis, we included all significant parameters from the univariate analyses that correlated with survival.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in accordance with prior studies [2,8,9] . For the multivariable analysis, we included all significant parameters from the univariate analyses that correlated with survival.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, combining all these cases into one group carries important limitations. However, population-based studies have shown that the histological subtype of urethral carcinoma does not appear to exert an impact on prognosis [1,2,8,9] . Nonetheless, it has to be acknowledged that urethral cancer is a rare disease for which therapeutic strategies still need to be better defined [12] .…”
Section: Discussionmentioning
confidence: 99%
“…5 The median interval from onset of symptoms to diagnosis is about 4.5 months. 1 The proximal one-third of the female urethra is lined by transitional epithelium, the distal two-thirds by stratified squamous epithelium. Accordingly, the histology of urethral tumours is generally consistent with the location.…”
Section: Discussionmentioning
confidence: 99%
“…6 Spread of urethral carcinoma also follows the anatomic subdivision: the anterior/distal female urethra drains primarily to the inguinal nodes; the mid-and proximal urethra drains to the external iliac and deep pelvic lymph nodes. 1 Female urethral carcinoma is rare, with a poor prognosis; it has a 5-and 10-year survival rate of 32% to 51% and 31% to 42%, respectively. 8 Data on this topic are limited, composed mostly of small case series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation